LAMA MASA KERJA DAN MANAJEMEN WAKTU DENGAN PELAKSANAAN DOKUMENTASI ASUHAN KEPERAWATAN - dewi, ratna; Maigeni, Maigeni (REAL in Nursing Journal, 2018)
This hospital has not been optimal in doing nursing care documentation. This study aimed to determine some factors related to nursing care documentation in the Inpatient Room of DR. Achmad Darwis Suliki in 2018. The study desing was a descriptive study analytical approach cros sectional. Total number of samples using a sampling technique is a way of collecting a sample based on the overall population of 42 nurses there. Then, by using total sampling technique, those people were chosen as the samples. The data were collected through questionnaires and observation sheets. The results of this reseach showed that 66.7% of respondents were graduated from Diploma III of Nursing program. Then, 50% of them had less that 3 years working period. Next, 52.4% of the respondents had poor time management. Last, 54.8% of them were not good nursing care documentation. Moreover, there was a correlation between education level (p = 0.037, OR = 5.278), working period (p = 0.013, OR = 6.4) and time management (p = 0.032, OR = 4.952) toward documentation of nursing care. The conclusion of this study is that there is a significant relationship between the length of service of nurse and nursing care documentation. Then, it is expected to all parties, especially the managerial nursing department of Dr. Ahmad Darwis Suliki always improve the performance of nurses in documenting nursing care through nursing training and seminars. Keywords : Working Experiences, Time Management  of Nursing Care Documentation